Practicing creative thinking and its relation to academic achievement - Ayasrah, Samer; Obeidat, Mutawakil; Katatbeh, Qutaibeh; Aljarrah, Abdalrahman; Al-Akhras, Mohammed-Ali (Creativity Studies, 2023)
Creativity is essential for survival and it is the path to progress and prosperity. Their creativity, innovation, invention and leadership measure the progress and development of nations.Creative thinking is one of the finest and highest skills and abilities that should be acquired by students in all different academic levels. The main objective of this study is to disclose the extent of practicing creative thinking and its relationship to academic achievement among students of the Jordan University of Science and Technology. The study was conducted on a sample of 1159 male and female students, who were chosen randomly. The study involved the following main question: To what extent are students of Jordan University of Science and Technology practicing creative thinking? It also contained three hypotheses: 1) There is a significant difference of practicing creative thinking among the students of Jordan University of Science and Technology due to gender; 2) There is a significant difference of practicing creative thinking among students of Jordan University of Science and Technology due to academic year; 3) There is a significant correlation between practicing creative thinking among students of Jordan University of Science and Technology and academic achievement. The results of the study indicated that students of Jordan University of Science and Technology are practicing creative thinking at a moderate level reaching 2.96 at Likert scale. Moreover, it revealed that there is a statistically significant difference in the level of practicing creative thinking due to gender favoring male students. A close relationship between the level of practicing creative thing and academic achievement was found, where 20% of the research sample having high academic achievement showed moderate level of practicing creative thinking.